Ketamine and propofol: safe for short procedures - Borkar Patil, Vijaya P.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2019)
Background: Patients who attend the hospital for any form of operative procedure frequently undergo physical or mental pain and agitation. These patients are extremely anxious. It is important to choose the most appropriate form of anesthesia for induction for the analgesia or sedation. This study examined the safety and effectiveness of the Ketamine and Propofol combination technique for short procedures like D and C, MTP, evacuation and marsupilisation of Bartholin’s abscess. Methods: The present observational study was carried out in association with the Gynecology and Obstetrics department and Department of Anesthesiology of PDMMC and hospital, Amravati, Maharashtra, India over a period of 3 months from 1st January to 31st March 2019. Results: In present study, 28 (56%) patients were of 25-40 years age, 14 (28%) patients were of 41-50 years age while 8 (16%) patients were of 51-60 years age. 7 (14%) patients were underweight, 26 (52%) patients had normal BMI, 10 (20%) patients were overweight while 7 (14%) patients were obese. MAP before surgery was 100 ± 12, which decreased to 92±9.2 during operation and increased to 97±19.4 in the postoperative period. Heart rate and arterial SPO2 were not significantly different before, during, and after the operation. Mean VAS score for pain was 5.2±5.1 and the mean Ramsay’s score of sedation was 5.8 ± 0.01. 1 (2%) patient had apnea, 1 (2%) patient had skin reaction, 1 (2%) patient had cough, 1 (2%) patient had agitation while 2 (4%) patient had nausea and vomiting. Conclusions: Ketamine and Propofol combination technique can be recommended for use in the short procedures safely and effectively.